2016
DOI: 10.1007/978-3-319-50832-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Motion of Oriented Magnitudes Patterns for Human Action Recognition

Abstract: In this paper, we present a novel descriptor for human action recognition, called Motion of Oriented Magnitudes Patterns (MOMP), which considers the relationships between the local gradient distributions of neighboring patches coming from successive frames in video. The proposed descriptor also characterizes the information changing across different orientations, is therefore very discriminative and robust. The major advantages of MOMP are its very fast computation time and simple implementation. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…By several hundred test cases where the recognition rates are calculated on 300 KTH action videos with different parameters, we found that the optimal parameters, as follows: Feature extraction – MOMP descriptor: we follow the same experimental settings as in [23]: o Step 1: Number of orientations d=5 is used to compute gradient and quantise orientation. o Step 2: We accumulate the magnitude of the pixels from their neighbours by Gaussian filter with the kernel size 5×5 and the standard deviation σ=1. o Step 3: We encode the features based on LTP‐based self‐similarity and the SSD of gradient magnitudes among successive frames. To calculate SSD, we choose a cell size r×r, r=3; the number of neighbouring cells in each block n=8 and a threshold T=r×r×τ2 (where r×r is cell size, the threshold τ is varying from 5 to 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By several hundred test cases where the recognition rates are calculated on 300 KTH action videos with different parameters, we found that the optimal parameters, as follows: Feature extraction – MOMP descriptor: we follow the same experimental settings as in [23]: o Step 1: Number of orientations d=5 is used to compute gradient and quantise orientation. o Step 2: We accumulate the magnitude of the pixels from their neighbours by Gaussian filter with the kernel size 5×5 and the standard deviation σ=1. o Step 3: We encode the features based on LTP‐based self‐similarity and the SSD of gradient magnitudes among successive frames. To calculate SSD, we choose a cell size r×r, r=3; the number of neighbouring cells in each block n=8 and a threshold T=r×r×τ2 (where r×r is cell size, the threshold τ is varying from 5 to 7).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the contribution of the feature post‐processing – PCA and feature selection – some filter methods, we compare the results on different systems separately in ours 1, ours 2, and ours 3. Ours 1 [23], which integrates our descriptor MOMP to VLAD and rbf‐SVM, obtains 94.4%. In comparison to ours 1, ours 2 has a better result (95.4%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the taxonomy proposed by Goodfellow et al [26], the approaches to this problem can be categorized into two groups: (i) traditional methods [6,56,77,92], where the action representation is explicitly chosen and the action recognition is defined under conventional machine learning algorithms, and (ii) representation-learning strategies that explore machine learning techniques for both tasks. The latter includes shallow approaches, such as dictionary-based methods [44,55,57,83], and deep learning strategies [33,34,35,50,59,67].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%